EDMODO GO BLOG - Rini Ekayati; Muhammad Arifin (Universitas Negeri Medan, 2018)
AbstractThe main issue laid behind this community service program is the fact that there is still low quality of learning and teaching activities which currently faced by Muhammadiyah schools in Binjai. This condition affects the quality of learning which is not optimally conducted, and so produce less than maximum learning results. Moreover, the development of science and technology now days affects the situation as well, where science and technology has been used in learning through the use of information-technology-based (IT-based) media. A training program on how to accommodate IT-based media is one solution offer to overcome this situation. The training materials provided include on making virtual classroom learning using Edmodo application, and connecting Edmodos with Blog in learning. This activity was held in Muhammadiyah complex building with 21 participants. Lecturing, discussions, and direct practice are the methods used in this program. At the end of the program, the participants had changed in the way they carried out their tasks in the class that have been utilizing IT-based media, so that the learning process is more qualified. This results shows that there is an improvement in the quality of teaching and learning process at Muhammadiyah schools in Binjai as program partners.Keywords: information technology-based media, Edmodo, Blog